2018
DOI: 10.7759/cureus.2290
|View full text |Cite
|
Sign up to set email alerts
|

Premenstrual Syndrome: Existence, Knowledge, and Attitude Among Female University Students in Karachi

Abstract: Objective The aim of this study was to investigate the existence, knowledge, and the attitude of female students towards premenstrual syndrome (PMS). Methods This cross-sectional study was conducted in three universities in Karachi, Pakistan. A total of 448 female students participated in the study. The clinical criterion of American College of Obstetricians and Gynecologists (ACOG) for PMS was used to assess the prevalence of PMS in the participants. The questionnaire was set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
21
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 17 publications
(16 reference statements)
7
21
1
1
Order By: Relevance
“…Regardless of severity, the ten symptoms most often occurring among the participants include: skin disorders, irritability, fatigue, mood swings, general aches and pains, lowered school or work performance, backache, painful breasts, weight gain, and swelling. The results of our study agree with those reported in earlier studies, which indicate that regardless of ethnicity, women in their late teens and early twenties frequently experience such premenstrual complications [4, 19, 21, 24, 26, 28]. As to the severity, epidemiological surveys found a certain percentage (7.7–26.6%) of college students suffering from PMDD—a particularly severe form of PMS defined as a distinct premenstrual affective disorder [29, 30].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Regardless of severity, the ten symptoms most often occurring among the participants include: skin disorders, irritability, fatigue, mood swings, general aches and pains, lowered school or work performance, backache, painful breasts, weight gain, and swelling. The results of our study agree with those reported in earlier studies, which indicate that regardless of ethnicity, women in their late teens and early twenties frequently experience such premenstrual complications [4, 19, 21, 24, 26, 28]. As to the severity, epidemiological surveys found a certain percentage (7.7–26.6%) of college students suffering from PMDD—a particularly severe form of PMS defined as a distinct premenstrual affective disorder [29, 30].…”
Section: Discussionsupporting
confidence: 93%
“…Although research designs and methods differ among the studies, and most of them are based on retrospective rather than prospective recording, the findings have been reasonably congruent. They indicate that nearly 90% of women of reproductive age experience at least one cyclical premenstrual symptom [2, 4, 19, 26, 27]. The present study demonstrated that, with one exception, 199 students (99.5%) experienced at least one symptom listed on the MDQ premenstrually.…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…The other studies reported similar findings to ours. In a Karachi study that involved medical students, the participants were found to have good understanding of PMS [24]. In contrast, the women in three metropolises of Pakistan were found to have limited knowledge of PMS [25].…”
Section: The Respondents' Knowledge Of Pms and Its Managementmentioning
confidence: 99%
“…Many of the respondents knew that PMS could adversely affect quality of life. In a cross-sectional study conducted among female university students in Karachi, 60.4% of the participants reported that PMS affected their normal routine, 35.4% reported missing school or work, and 40.2% reported missing social events because of PMS [24].…”
Section: The Respondents' Knowledge Of Pms and Its Managementmentioning
confidence: 99%